Upaya Meningkatkan Hasil Belajar Perkalian melalui Media PKP2 (Papan Kantong Pintar Perkalian) Kelas II SDN 3 Sepatan - Zuliani, Rizki; Safitri, Agustini; Nur’Azizah, Laily Yuniar (MASALIQ, 2023)
Education is the main factor for forming the potential of a knowledgeable and civilized human being. Because, education is a process to form someone who can be formed into a human being who has knowledge, the role of education is also very important for someone to hone the skills and abilities of students to be able to solve their own problems. In carrying out education, learning media is also needed with the aim of being able to make it easier for students to understand the material taught by the teacher. From this understanding, it can be said that teaching material without preparing methods and media will not be appropriate and teaching and learning activities will not run effectively and efficiently so that the material that will be conveyed by the teacher to students will not be absorbed optimally. This multiplication PKP2 media is a media that is deliberately made to give a different nuance when the teaching and learning process takes place, in this media it also aims to make students enthusiastic when receiving multiplication lessons. Actually this media can be used for other subjects as well, so this smart pocket media is not only used for Indonesian lessons but can also be used for other lessons.